ANALISIS PENGARUH KEBIJAKAN DIVIDEN, BVPS, EARNING VOLATILITY, LEVERAGE, PER, DAN VOLUME PERDAGANGAN TERHADAP VOLATILITAS HARGA SAHAM (Studi Empiris Pada Perusahaan Go Public Non Keuangan Yang Listing di Bursa Efek Indonesia Tahun 2012-2015) - Mobarak, Rizqin; Mahfud, Mohammad Kholiq (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to analyze the influence of Dividend Policy, BVPS, Earning Volatility, Leverage, PER, and Trading Volume to Stock price Volatility on the company non financial in Indonesian Stock Exchange in period 2012-2015. Research population used company non financial in Indonesian Stock Exchange in period 2012-2015. Taken samples of the all purpose 28 companies by using purposive sampling method. The data used in this research were obtained from the Indonesian Capital Market Directory (ICMD) 2012-2015, IDX Annual Report, and www.idx.co.id. Analysis technique used Ordinary Least Square Regression (OLS), statistical t-test, f-test, and classic assumption test that includes a test of normality test, multicollinearity test, autucorrelation test, and heteroskedastisitas test. The result of the research are independent variables simultaneously (F test) effect on stock price with a significance level of 0.000. While partially (t test) showed that the variable Dividend Payout Ratio and BVPS has positive and not significant effect on Stock Price Volatility. Earning Volatility and PER variables has negative and significant effect on Stock Price Volatility. While Leverage and Trading Volume has positive and significant effect on Stock Price Volatility. Adjusted R2 is 0,216 wahich means that the ability of the six independent variables can explain Stock Price Volatility amounted to 21,6%, while the rest is explained by other factors.